Development of an Automatic Combination System of Clothing Parts for Blind People: MyEyes - Rocha, Daniel (2018)
Blind people have been, over time, a reason for motivation in the development of solutions to improve their quality of life. The aim of this work is to propose a solution for one of such problems, namely, the selection and combination of clothing for the blind. Thus, this paper describes the whole project developed, in agreement with the Portuguese Association of the Blind and Amblyopic of Portugal (ACAPO), for the creation of a Web platform to aid the blind in selecting combinations of clothing. Near Field Communication (NFC) technology is the basis of this project in the identification of garments. The features of the garments are inserted manually, and a combination of features is possible. There is also the possibility to automatically identify the color of the garment. The system has been tested by the ACAPO organization and preliminary feedback is positive, which are a good starting point for the future. This solution helps promote an increased autonomy for blind people.